1990
DOI: 10.1203/00006450-199009000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aminophylline on Diaphragmatic Contractility in the Piglet

Abstract: ABSTRACT. Minute ventilation, arterial blood gases, ar-of arterial oxygen > 8 kPa (60 torr) in room air, and a partial terial pH, cardiac output, and transdiaphragmatic force pressure of the arterial carbon dioxide 5 6.7 kPa (50 torr) were generation, both during spontaneous ventilation and in accepted for study. The animals were anesthetized with an i.v. response to phrenic nerve stiwulation during airway occlu-combination of chloralose (30 mg/kg) and urethane (1 50 mg/ sion at end expiration, were measured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…33], and a third group of studies found an increase in force at low but not high stimulation frequen cies [9, 10, 15. 19], This discrepancy among studies can not be easily explained on the basis of species or méthodo logie differences, although of note is that one study per formed on neonatal diaphragm (piglet) found no im provement in force with aminophylline [33]. The present study was not specifically designed to resolve this contro versy for the diaphragm, but nonetheless suggests that theophylline does not augment the twitch force of the pha ryngeal dilator musculature.…”
Section: Discussionmentioning
confidence: 71%
“…33], and a third group of studies found an increase in force at low but not high stimulation frequen cies [9, 10, 15. 19], This discrepancy among studies can not be easily explained on the basis of species or méthodo logie differences, although of note is that one study per formed on neonatal diaphragm (piglet) found no im provement in force with aminophylline [33]. The present study was not specifically designed to resolve this contro versy for the diaphragm, but nonetheless suggests that theophylline does not augment the twitch force of the pha ryngeal dilator musculature.…”
Section: Discussionmentioning
confidence: 71%
“…The accuracy of techniques used in this study to determine the pressure-generating capability of the diaphragm have previously been critiqued (18,25). The PdiFC was used to assess Pdi generation.…”
Section: Resultsmentioning
confidence: 99%